Analysis of Large-Scale Social Restrictions During the Covid-19 Pandemic on the Implementation of Worship Using the Ushul Fikih Approach - M. Junaidi; Fitri Dzakiyya (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
The corona virus is sweeping the world. Such rapid transmission from human to human causes quite a few fatalities. Generally, based on research, this virus spreads through droplets and disease transmission through direct contact with sufferers. While a vaccine and medicine have not yet been found, the concrete step taken is to break the chain of spread of the virus. Therefore, various countries have taken policies in an effort to stop the spread of the virus. Indonesia is no exception, as an affected country it has also issued a Large-Scale Social Restrictions (PSBB) policy. These rules regulate various aspects ranging from education, work to worship. In the field of worship, this regulation requires the temporary elimination of worship in places of worship and replacing it with worship at home. This rule raises pros and cons in society. Some people believe that eliminating worship in places of worship is inappropriate because other public places such as markets are still open. Using the library research method and using the approach of Islamic jurisprudence principles and ushul jurisprudence, this paper analyzes this policy. The results of this research show that the policy of eliminating worship in places of worship during the pandemic does not conflict with Islamic law. Apart from that, to issue other policies in dealing with this pandemic, based on Islamic law, protecting the soul (hifzh al-nafs) is prioritized over protecting property (hifzh al-mâl).